Dramatic loss of forest-dependent bird species from Semenggoh Nature Reserve, Sarawak, over 60 years - Hanis Damia Elyna, Lit; Mohd Azlan, Jayasilan; RICHARD, A. Noske (Oriental Bird Club Secretary, 2023)
The species composition and abundance of birds at Semenggoh Nature Reserve, Sarawak, was examined using mist-nets over 14 months during 2015–2016, and compared to results obtained by Fogden (1976), who mist-netted birds there over 14 months in 1964–1965. We mistnetted 55 species, including nine that were not recorded by Fogden, seven of which are common colonisers of anthropogenic habitats. In striking contrast, Fogden captured or observed 139 species, 93 (62.8%) of which were not recorded in our mist-netting study. Up to May 2021, eBird contained records of 186 species among 133 lists submitted by 54 observers. Combining all data sources yields a grand total of 223 species for Semenggoh, 75 of which were recorded only in eBird, although 43 of these species involved only one or two sightings over 42 years of records, and 47 species are non-dependent on forests. On the other hand, 37 species recorded by Fogden in 1964–1965 were missing from eBird lists. Although we captured or observed eight of these species, it seems likely that that the remaining 29, of which 25 (86%) are forest-dependent, have been extirpated from Semenggoh since 1965. Moreover, up to 10 additional forest-dependent species recorded by Fogden may have disappeared in the decade since 2004, suggesting that up to 39 species have been lost from this protected area. Nevertheless, Semenggoh still has considerable conservation value, with 182 species being recorded since 2013, including three Endangered and five Vulnerable species, and thus deserves full protection.